Watershed Classification Predicts Streamflow Regime and Organic Carbon Dynamics in the Northeast Pacific Coastal Temperate Rainforest. Issue 2 (16th February 2022) - Giesbrecht, Ian J. W.; Tank, Suzanne E.; Frazer, Gordon W.; Hood, Eran; Gonzalez Arriola, Santiago G.; Butman, David E.; D'Amore, David V.; Hutchinson, David; Bidlack, Allison; Lertzman, Ken P.
Abstract: Watershed classification has long been a key tool in the hydrological sciences, but few studies have been extended to biogeochemistry. We developed a combined hydro‐biogeochemical classification for watersheds draining to the coastal margin of the Northeast Pacific coastal temperate rainforest (1, 443, 062 km 2 ), including 2, 695 small coastal rivers (SCR) and 10 large continental watersheds. We used cluster analysis to group SCR watersheds into 12 types, based on watershed properties. The most important variables for distinguishing SCR watershed types were evapotranspiration, slope, snowfall, and total precipitation. We used both streamflow and dissolved organic carbon (DOC) measurements from rivers ( n = 104 and 90 watersheds respectively) to validate the classification. Watershed types corresponded with broad differences in streamflow regime, mean annual runoff, DOC seasonality, and mean DOC concentration. These links between watershed type and river conditions enabled the first region‐wide empirical characterization of river hydro‐biogeochemistry at the land‐sea margin, spanning extensive ungauged and unsampled areas. We found very high annual runoff (mean > 3, 000 mm, n = 10) in three watershed types totaling 59, 024 km 2 and ranging from heavily glacierized mountain watersheds with high flow in summer to a rain‐fed mountain watershed type with high flow in fall‐winter. DOC hotspots (mean > 4 mg L −1, n = 14) were found in three other watershed types (48, 557 km 2 ) with perhumid rainforest climates and less‐mountainous topography. We described four patterns of DOC seasonality linked to watershed hydrology, with fall‐flushing being widespread. Hydro‐biogeochemical watershed classification may be useful for other complex regions with sparse observation networks. Plain Language Summary: Watersheds transfer large amounts of freshwater to the ocean, yet each watershed does this differently from the next. Geographic differences in climate and topography affect the global biogeochemical cycling of elements like carbon. However, most rivers in regions like the carbon‐dense rainforest of western North America have no measurements of streamflow or carbon, making it hard to predict how river dynamics change across geographic locations. Our goal was to classify and map watershed types for an entire coastal region, with consideration of both water and carbon. Our results show the locations of watershed types with very different amounts and seasonality of runoff and of dissolved organic carbon (DOC). While we focused on DOC, these watershed types might naturally differ in other aspects of river biogeochemistry such as organic nitrogen and iron. Maps of watershed types should help society understand how land and sea are linked together over complex regions within a changing climate. However, certain watershed types have little or no long‐term monitoring to guide climate adaptation. While many studies have classified watersheds from a hydrology perspective, few have considered carbon as well. Combining hydrology and biogeochemistry when mapping watershed types may be useful in other regions of the world. Key Points: Unsupervised classification of 12 watershed types based on watershed properties predicts aspects of river hydrology and biogeochemistry Climate and topography create complex spatial mosaics of watershed types, streamflow regimes, and dissolved organic carbon dynamics Watershed classification for hydro‐biogeochemistry may be useful for predictive mapping in other complex regions with sparse observations